Delay in Antibiotic Administration Is Associated With Mortality Among Septic Shock Patients With Staphylococcus aureus Bacteremia*. Issue 4 (April 2020) - Corl, Keith A.; Zeba, Fatima; Caffrey, Aisling R.; Hermenau, Matthew; Lopes, Vrishali; Phillips, Gary; Merchant, Roland C.; Levy, Mitchell M.; LaPlante, Kerry L.
Abstract : Objectives: The relationship between the timing of antibiotics and mortality among septic shock patients has not been examined among patients specifically with Staphylococcus aureus bacteremia. Design: Retrospective analysis of a Veterans Affairs S. aureus bacteremia database. Setting: One-hundred twenty-two hospitals in the Veterans Affairs Health System. Patients: Patients with septic shock and S. aureus bacteremia admitted directly from the emergency department to the ICU from January 1, 2003, to October 1, 2015, were evaluated. Interventions: Time to appropriate antibiotic administration and 30-day mortality. Measurements and Main Results: A total of 506 patients with S. aureus bacteremia and septic shock were included in the analysis. Thirty-day mortality was 78.1% for the entire cohort and was similar for those participants with methicillin-resistant S. aureus and methicillin-sensitive S. aureus bacteremia. Our multivariate analysis revealed that, as compared with those who received appropriate antibiotics within 1 hour after emergency department presentation, each additional hour that passed before appropriate antibiotics were administered produced an odds ratio of 1.11 (95% CI, 1.02–1.21) of mortality within 30 days. This odds increase equates to an average adjusted mortality increase of 1.3% (95% CI, 0.4–2.2%) for every hour that passes before antibiotics are administered. Conclusions: The results of this study further support the importance of prompt appropriate antibiotic administration for patients with septic shock. Physicians should consider acting quickly to administer antibiotics with S. aureus coverage to any patient suspected of having septic shock. Abstract : Supplemental Digital Content is available in the text.